1994
DOI: 10.1103/physrevb.49.7898
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport studies of pureV2O3under pressure

Abstract: We report a systematic study of the resistivity and magnetic susceptibility of pure V,O3, the original Mott-Hubbard system at half filling, for pressures 0(P~25 kbar and temperatures 0.35 T 300 K.We also study {V099Tipp&)203 under pressure in order to elucidate the role of disorder on a metalinsulator transition in the highly correlated limit. Despite the low level of doping, we find that the two systems are very different. We observe a conventional collapsing of the Mott-Hubbard gap only for stoichiometric Vq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…23,[31][32][33] The transition temperature decreases rapidly under pressure. 34 A pressure of only 9 kbar lowers the transition temperature by 60 K, and the transition is completely suppressed at a pressure of Ϸ20 kbar. 34 The transition temperature is also rapidly suppressed if the sample contains V vacancies; a crystal of composition V 1.985 O 3 showed a transition temperature of Ϸ50 K. 33 Furthermore, it was found that when V 2 O 3 is epitaxially grown on LiTaO 3 , the transition temperature is enhanced from the bulk value by 20 K. 25 Given the possibilities of compressive or tensile stresses acting on the V 2 O 3 due to the epitaxial relationship of the V 2 O 3 impurity with the CaV 2 O 4 host and the possibility of nonstoichiometry of the V 2 O 3 impurity phase, one can see how the transition temperature of the V 2 O 3 might be depressed or enhanced from the bulk value by Ϸ30 K as we found for the coherently grown V 2 O 3 impurity phases in our two annealed crystals in Sec.…”
Section: A Origin Of the Transition At T S1 è 200 K In Annealed Cav mentioning
confidence: 98%
“…23,[31][32][33] The transition temperature decreases rapidly under pressure. 34 A pressure of only 9 kbar lowers the transition temperature by 60 K, and the transition is completely suppressed at a pressure of Ϸ20 kbar. 34 The transition temperature is also rapidly suppressed if the sample contains V vacancies; a crystal of composition V 1.985 O 3 showed a transition temperature of Ϸ50 K. 33 Furthermore, it was found that when V 2 O 3 is epitaxially grown on LiTaO 3 , the transition temperature is enhanced from the bulk value by 20 K. 25 Given the possibilities of compressive or tensile stresses acting on the V 2 O 3 due to the epitaxial relationship of the V 2 O 3 impurity with the CaV 2 O 4 host and the possibility of nonstoichiometry of the V 2 O 3 impurity phase, one can see how the transition temperature of the V 2 O 3 might be depressed or enhanced from the bulk value by Ϸ30 K as we found for the coherently grown V 2 O 3 impurity phases in our two annealed crystals in Sec.…”
Section: A Origin Of the Transition At T S1 è 200 K In Annealed Cav mentioning
confidence: 98%
“…29,30 This results in zero overall magnetic moment, event though individual layers have a relatively high moment of 1.2 B per vanadium atom. Experiments 31 have shown that the magnetic transition can be shifted to a temperature below 150 K by application of pressure. At a pressure of about 15 kbar the magnetic transition decouples from the metal-insulator transition, and by about 26 kbar, both phase transitions are completely suppressed.…”
Section: B Characterizationmentioning
confidence: 99%
“…This is in contrast to doping narrow band systems where the complications of electronic and structural disorder lead to effects that may not occur with pressure [ 5 ] .…”
Section: Introductionmentioning
confidence: 99%